Análise da governança: o caso da cadeia produtiva do biodiesel no Rio Grande do Sul - Bergamo, Estefane da Silveira (Universidade do Vale do Rio dos Sinos, 2010)
The importance of biodiesel in Brazil is not only related to environmental issues, but it is also linked to the social inclusion of family farming. In order to achieve social inclusion, the Federal Government created the “Programa Nacional de Produção e Uso do Biodiesel – PNPB” (National Program of Biodiesel Production and Use) which promotes the production of this new fuel in the Brazilian energy matrix. Rio Grande do Sul, as one of the largest producers of soybeans in the country, has introduced this vegetable as the main raw material for biodiesel production. The current project is based on a case study of governance of the biodiesel productive chain in Rio Grande do Sul, which describes the current biodiesel production chain in the state. For this, this paper analysed a model of governance of the production chain into two segments: industrial and agricultural using the methodology presented in the research. It’s important to understand the governance in the production chain, so that a strategy of production can be planned and explored more effectively at every link in the chain. The objective of this research is to characterize and analyse the governance of two segments of the global value chain as well as the governance of global value chain of biodiesel in Rio Grande do Sul. In addition, the project intends to know which actors play the leading parts within the production chain. The research is a unique case study because it only studies the local production chain and one kind of raw material that belongs to this chain. In order to understand the view of governance of each of the leading actors in the chain and characterize the production chain as a whole, it was used a customised questionnaire for each actor in the chain. A global value chain driven by the buyer and a structure of modular governance were the results obtained with this instrument.
Keywords: Governança; Cadeia global de valor; Biodiesel; Governance; Global value chain; ACCNPQ::Engenharias::Engenharia de Produção